Compact and sustainable electronic module for silicon photodetectors - Sadigov, A; S. Nuruyev, S. Nuruyev; Akbarov, R.; Berikov, D.B.; Madadzada, A.; Mammadli, A.; Lyubchyk, S.; Yilmaz, E. (Eurasian Journal of Physics and Functional Materials, 2026)
This article presents the development of a cost-effective and efficient electronic module for silicon photodetectors (SiPM). The electronic module combines essential functionalities, such as a high voltage power supply, a preamplifier, and a signal comparator, into a compact circuit. A high voltage power supply with a range of 30 to 140 V provides a stable bias voltage with 0.01 V accuracy, while a preamplifier with 40 gain and 250 MHz bandwidth enables signal amplification necessary to extract weak signals. The comparator converts an analogue signal (higher than 8 mV) into TTL (transistor-transistor logic), which makes it easy to process and analyze with digital devices such as microcontrollers or make it possible to send signals over long distances by a cable. The module has been tested using an LYSO scintillator and a silicon photomultiplier (SiPM) called a micropixel avalanche photodiode (MAPD). It provides a more effective and efficient solution for reading out signals from SiPMs in a variety of applications, delivering reliable and accurate results in real-time.Recommended CitationSadigov, A.; Nuruyev, S.; Akbarov, R.; Berikov, D. B.; Madadzada, A.; Mammadli, A.; Lyubchyk, S.; and Yilmaz, E. (2023) "Compact and sustainable electronic module for silicon photodetectors," Eurasian Journal of Physics and Functional Materials: Vol. 7: No. 3, Article 2.DOI: https://doi.org/10.32523/ejpfm.2023070302